The relationship between leadership behavior and burnout among coaches and athletes - Rad, L. S.; Ghalenoei, S. (European Journal of Experimental Biology, 2013)
Recently, burnout in sport has received increasing attention, to the point that some scholars have even suggested that burnout has become synonymous with sports (Lai & Wiggins, 2003). The present research examines the relationship between leadership behavior and burnout among coaches and athletes. The population consisted of 218 swimmers and 50 coaches who participated in intercollegiate competitions. The participants completed a demographics questionnaire, Maslach Burnout Inventory (MBI), the Athlete Burnout Questionnaire (ABQ) of Raedeke and Smith (2001), and the Leadership Scale for Sports (LSS) of Chelladurai (1980). One-sample t-test and histogram charts were used to examine the differences between variables. Pearson correlation coefficient was used at the0.05 significance level for hypothesis testing. The findings showed that there is no significant relationship between autocratic leadership and burnout among coaches. The subscales of autocratic leadership, however, were negatively associated with depersonalization and positively associated with reduced personal accomplishment. A significant relationship was observed between leadership style of coaches and burnout among athletes. Athlete burnout was negatively associated with training and instruction, negatively associated with positive feedback, and positively associated with autocratic behavior. Autocratic behavior was positively associated with all the three components of burnout among athletes. No significant relationship was observed between coach burnout and athlete burnout, but weak correlations were observed between coach burnout and reduced personal accomplishment and emotional exhaustion of athletes